61. How does the public in Latin American countries view genetic and genomic data donation for research? - Chavarría Soley, Gabriela (2022)
Large amounts of genetic and genomic data are constantly being generated in different contexts. Making this data available for research purposes is an attractive concept with many potential benefits, but which also raises concerns. The availability of such data depends firstly on the willingness of the persons whose genetic data is being generated to share it. The “Your DNA, Your Say” anonymous online survey explores attitudes of the public regarding different aspects of genomic and medical data donation for research, and the factors that influence the decision whether to donate. It has been translated into 15 languages and has been answered by individuals from more than 20 countries.